Optimal utilization of unified power quality conditioner using the JAYA optimization algorithm. Issue 1 (2nd January 2023) - Gade, Swati; Agrawal, Rahul
Abstract : In modern power systems, the unified power quality conditioner (UPQC) is the most attractive and promising solution for mitigating the power quality problem. Increasing utilization of dynamic voltage restorers (DVRs) for active–reactive power sharing in all operating conditions reduces the burden on UPQC and results in improved efficiency and reliability of the system. By controlling the power angle between source and load voltage, VA loading of a DVR can be controlled. This article presents a novel algorithm using variable phase angle control based on JAYA optimization (Jaya is a Sanskrit word meaning victory or triumph). The main objective is to determine an optimum power angle at which VA loading of the UPQC will be minimum without compromising the compensation capabilities. The performance of UPQC with JAYA optimization has been compared with the particle swarm optimization and teaching learning based optimization algorithms, and without optimization approaches to show the effectiveness of the proposed algorithm. This research work will help to develop an instantaneous VA loading based efficient control strategy for UPQC.